Human Capital and Economic Growth in Sub-Saharan African Countries: A Panel Data Analysis - Bashir Elsharif, Mohamed Sharif; Ali, Adil Idris Mohamed; Abdelhadi Hassan Elamin , Ahlam (Journal of Economics and Administrative Sciences, 2024)
Purpose: This study examined the empirical relationship between human capital and economic growth across eight Sub-Saharan African (SSA) countries from 1990 to 2022.Theoretical Framework: This study examined the relationship between human capital and economic growth by applying the Cobb-Douglas production function within the framework of the neoclassical Solow growth model. The study considers fixed assets as a measure of physical capital and school enrollment as a proxy for human capital.Design/Methodology/Approach: This study employed the pooled mean group (PMG) estimator within a panel autoregressive distributed lag (ARDL) approach to analyze human capital variables' short- and long-run impacts on economic growth in SSA countries.Findings: The findings provided strong empirical evidence of significant short- and long-term relationships between the variables. The long-run analysis demonstrates that human capital positively influences economic growth. Additionally, in the short-run, fixed assets, human capital, and labor were found to positively and significantly impact economic growth.Research Implications: This study emphasizes the importance of focusing on education and skill training sectors to enhance human capital development in emerging African countries.Originality/Value: This study demonstrates that human capital variables positively impact economic growth in SSA countries in both the short- and long-run. Consequently, this study underscores the role of human capital as a critical and influential factor in promoting economic growth in emerging SSA countries. It also contributes valuable insights for policymakers and adds to the existing literature in this area.